2018
DOI: 10.1109/tcns.2018.2796301
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Decision-Making Dynamics Inspired by Honeybees

Abstract: Abstract-When choosing between candidate nest sites, a honeybee swarm reliably chooses the most valuable site and even when faced with the choice between near-equal value sites, it makes highly efficient decisions. Value-sensitive decision-making is enabled by a distributed social effort among the honeybees, and it leads to decision-making dynamics of the swarm that are remarkably robust to perturbation and adaptive to change. To explore and generalize these features to other networks, we design distributed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 30 publications
2
100
0
Order By: Relevance
“…For a fixed N , a large enough n, i.e., a large enough number of agents with disparity in thresholds, is necessary for the cascade. For n large enough that y 0 exists, we can expect that for ∈ [0, (y 0 , N, n)], the bifurcation is supercritical, since it is for = 0 [10]. As increases to greater than the critical value = (y 0 , N, n), we expect to see the transition from no cascade to cascade.…”
Section: Conditions For Cascadementioning
confidence: 99%
See 3 more Smart Citations
“…For a fixed N , a large enough n, i.e., a large enough number of agents with disparity in thresholds, is necessary for the cascade. For n large enough that y 0 exists, we can expect that for ∈ [0, (y 0 , N, n)], the bifurcation is supercritical, since it is for = 0 [10]. As increases to greater than the critical value = (y 0 , N, n), we expect to see the transition from no cascade to cascade.…”
Section: Conditions For Cascadementioning
confidence: 99%
“…1 shows a network with N = 11 and n = 4. With an approach similar to that in Theorem 4 of [10], it can be shown that the trajectories of (1) converge exponentially to the three-dimensional manifold where all the states in the same cluster are the same. Let y k be the average state of cluster k = 1, 2, 3.…”
Section: Continuous Threshold Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For certain nonlinear dynamical networks, especially those in ecology, closed-loop control can be articulated and has been demonstrated to be effective [40]. Recently, how to exploit biologically inspired agent based control method to choose different alternative states in engineered multiagent network systems has been studied [41].…”
Section: Introductionmentioning
confidence: 99%